Portrait of Tafsir Recitation at The Thariqul Jinan Mosque Dalan Lidang Village Panyabungan Subdistrict Mandailing Natal District - Ilmi AS, Mei Arina; Enghariano, Desri Ari; Simanjuntak, Dahliati (Perkumpulan Manajer Pendidikan Islam Indonesia (PERMAPENDIS) Prov. Sumatera Utara, 2025)
In modern times, especially in Indonesia, the development of the interpretation of al-Qur’an is increasingly rapid and his also appeared in formal education such as lectures, namely with special study programs on interpretation and exegesis courses. Not only that, now a days tafsir recitation is also included in the community’s routine activities as evidenced by existence of weekly or monthly tafsir recitations. The research by tittle Portrait of Tafsir Recitation at The Thariqul Jinan Mosque Dalan Lidang Village Panyabungan Subdistrict Mandailing Natal District, examines the methods used in the recitation, and the conregation’s response to the tafsir recitation. The aim of this research is to determine the methods used in interpretingrecitations and to be determine the congregation’s response to interpreting recitations at the Thariqul Jinan mosque, Dalan Lidang Village. This research is field research using qualitative methods and descriptive approaches. The primary data sources in this research are Ustadz Joharuddin, L.c, Tafsir recitation congregation, mosque administrators obtained from observation, interviews and documentation. Meanwhile, secondary data sources for this research are books, commentary books, and articles related to the theories in this research. Based on the research results, the author concludes that the tafsir recitation held at the Thariqul Jinan Mosque, Dalan Lidang Village, is a program from the instructors of the Ministry of Religion of Mandailing Natal District which is held twice a week, namely on Tuesday and Friday morning after the Fajr prayer for hours. Ah, at the mosque. This tafsir study was delivered by ustadz Joharuddin, L.c who referred to the book of tafsir Shafwah at-Tafasir the work of Sheikh Muhammad Ali ash-Shabuni. The method used in studying this interpretation is method al-Mujaz or al-Mukhtasar, which means conveying material simply and concisely. While the tafsir study community gave a good response to this tafsir study, they felt very helped to be able to study the Qur'an through this tafsir study, adding knowledge and insight and strengthening their Islamic brotherhood.